Composites post fabrication & joining - Society of Manufacturing Engineers ([Dearborn, MI] : Society of Manufacturing Engineers, 2005)
This program examines the various methods used to saw, cut, rout, and drill composites effectively. The use of adhesives and mechanical fasteners to join separate composite components together is also explored in details
Title from title screen
DVD format
Keywords: Composite materials; Composite construction; Manufacturing processes